2020
DOI: 10.3389/fonc.2020.591352
|View full text |Cite
|
Sign up to set email alerts
|

A Hematological-Related Prognostic Scoring System for Patients With Newly Diagnosed Glioblastoma

Abstract: BackgroundGlioblastoma is the most common primary malignant brain tumor. Recent studies have shown that hematological biomarkers have become a powerful tool for predicting the prognosis of patients with cancer. However, most studies have only investigated the prognostic value of unilateral hematological markers. Therefore, we aimed to establish a comprehensive prognostic scoring system containing hematological markers to improve the prognostic prediction in patients with glioblastoma.Patients and MethodsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The second area of focus was the longitudinal variability of these indicators throughout the disease course, including throughout treatment. By assessing how the NLR, PLR, and RDW fluctuated over time, we sought to gain perceptions of the disease's progression and the effectiveness of treatment modalities [23]. This longitudinal analysis is essential, as it may uncover temporal patterns that might serve as early indicators of treatment success or failure and could potentially predict disease recurrence or progression.…”
Section: Discussionmentioning
confidence: 99%
“…The second area of focus was the longitudinal variability of these indicators throughout the disease course, including throughout treatment. By assessing how the NLR, PLR, and RDW fluctuated over time, we sought to gain perceptions of the disease's progression and the effectiveness of treatment modalities [23]. This longitudinal analysis is essential, as it may uncover temporal patterns that might serve as early indicators of treatment success or failure and could potentially predict disease recurrence or progression.…”
Section: Discussionmentioning
confidence: 99%
“…The “net” constructed by FIB in the extracellular matrix promotes cell adhesion and tumor invasion ( 30 ); in addition, FIB ultimately promotes angiogenesis and tumor growth by binding to growth factors such as vascular endothelial growth factor and fibroblast growth factor-2 ( 31 , 32 ). Previous studies have found that a high level of DD induces the progression of oral squamous cell carcinoma, cervical cancer, and glioma ( 13 , 19 , 33 ). In our study, the AUCs of FIB and DD for the diagnosis of meningioma progression were 0.615 and 0.593 in the training cohort, respectively, and their weighting coefficients in the HRM were 0.199 and 0.712, respectively; this also confirmed that high levels of FIB and DD were risk factors for the progression of AM.…”
Section: Discussionmentioning
confidence: 99%
“…reported that preoperative neutrophil-to-lymphocyte ratio (NLR) and fibrinogen (FIB) were related to the PFS of patients with AM ( 11 ). Our previous study confirmed the prognostic value of lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and albumin-to-globulin ratio (AGR) in glioma ( 12 ); other factors, such as D-dimer (DD), hemoglobin (HBG), lactate dehydrogenase (LDH), and red blood cell distribution width (RDW), have also been shown to be correlated with clinical outcomes in patients with glioma ( 13 ). However, it remains unclear whether these parameters have any prognostic value in AM.…”
Section: Introductionmentioning
confidence: 99%